The co-evolution of technology and warfare reshaping the battlefield - German, Tracey C. 1971-; German, Tracey C. 1971-; Moustakis, Fotios 1970-; Moustakis, Fotios 1970-; Liaropoulos, Andrew N.; Liaropoulos, Andrew N. (Routledge, 2026)
"This book explores the relationship between technology and warfare, by examining how recent technological advancements have revolutionized the conduct of war. The work analyses contemporary conflicts, including the Syrian civil war, the Taliban takeover in Afghanistan, and the ongoing war in Ukraine, but also by exploring future war scenarios and assessing the military capabilities of major powers. In doing so, the book highlights the dynamic and evolving nature of modern warfare. It goes beyond a simple examination of technological advancements, addressing the complexities of modern warfare, scrutinizing the strategies employed by states to adopt and develop military technologies, while emphasizing the importance of technology in shaping military planning, training, research, and innovation. The book provides a collection of timely contributions by leading scholars and practitioners in the military and security field. Furthermore, the contributors identify potential challenges and risks associated with the widespread adoption of technologies in warfare and propose recommendations for policymakers to address issues that relate to military planning and training, research and development, and resilience building. This book will be of much interest to students of security studies, technology studies, defence studies and International Relations"-- Provided by publisher
Keywords: Military engineering; Technological innovations; Military art and science -- Technological innovations.; Military art and science -- History -- 21st century